Upaya Pencegahan Stunting melalui Sosialisasi dan Pembagian Poster ke Posyandu dan Puskesmas - Fitri Humairoh; Fuva Wersa Yolifi; Nesi Anggraini; Dyenda Azzahra; Rulli Septiawan; Sabrina Nur Fitri; Zahara Luthfia Niza; Surya Alhadi Alhadi; Maysha Juniati Hasanah; Sheila Salsabila; Ilham Fajri Rahmadian (Asosiasi Dosen Akuntansi Indonesia, 2022)
This community’s service activity is carried out in Perawang Barat village, a subdistrict of Tualang, regency of Siak. The purpose of this community’s dedicated activities to 1) provide information and education to the public about stunting and nutrition of the child, 2) increase the knowledge and insight of the community on the stunting prevention, 3) raising mothers’ awareness linked to child development early on. As for the benefits of this community’s devotion activity, it is to change people’s behavior to better understand what stunting is, why and prevention efforts are early, even from pregnancy. The targeted communities of these activities are expectant mothers, lactating mothers, and 0-23 months of age. The method used in community service activities is the socialization and division of stunting poster to posyandu and puskesmas. After the socialization and divison of posters, the executive team has established a group of chaperones and coaching about a stunting in order to see community knowledge and existing constraints so that if they have a problem, they can be eliminated immediately.